Penerapan Pembelajaran Matematika Realistik untuk Meningkatkan Hasil Belajar Siswa - Akina; Sulistiowati (PEDAGOGIKA, 2020)
This research aims to obtain a description of the application of Mathematic Realistic Learning (PMR) that can improve students learning outcomes on nets cubes and beams in class IV SDN Tanamodindi Palu. The type of this research is classroom action research. The design of this research referred to Kemmis and Mc. Teggart’s design. This research was conducted in two cycles. The results of this research indicating that through the application of realistic mathematic education that can improve student learning outcomes, by following the steps, as follow (1) present a contextual problem, (2) explain the contextual problem, (3) solving the contextual problem, (4) comparing and discuss answers, and(5) concluding.